Combining Clustering Methods With MPS to Estimate Structural Uncertainty for Hydrological Models - Vilhelmsen, Troels Norvin; Auken, Esben; Christiansen, Anders Vest; Barfod, Adrian Sanchez; Marker, Pernille Aabye; Bauer-Gottwein, Peter (Frontiers in Earth Science, 2019)
This study presents a novel expansion of the clay-fraction (CF)/resistivity clustering method aiming at developing realizations of subsurface structures based on multiple point statistics (MPS). The CF-resistivity clustering method is used to define a data driven training image (TI) for MPS simulations. By combining this TI with uncertainty estimates obtained from correlation between the resistivity models and the unique categories in the TI, subsurface realizations are generated honoring all geophysical and lithological data including any equivalent resistivity layer sequences. The generated subsurface realizations were calibrated in a steady state groundwater model. Forecasts of well catchment zones were derived based on two wells located in areas with different levels of structural uncertainty. The catchment probability maps derived from the structural realizations were compared with the well catchment forecasted by a deterministic subsurface structure, and we are able to capture this catchment within the estimated uncertainties. We believe that this study is the first to combine MPS methods with a complete data driven workflow going directly from lithological and geophysical data to realizations of the subsurface structures. The main benefits of this is that it is data driven, fast, reproducible, and transparent.